Changes in low back pain intensity following red ginger warm compresses among pregnant women in the third trimester: A pre-experimental study - Popi Lya Destari; Risqina Putri; Afrilia Fazrina; Afni Yan Syah; Che Azunie Che Abdullah (School of Health Sciences Al-Ma'arif, 2026)
Background: Pregnancy is a natural process experienced by every woman, during pregnancy the mother can experience various complaints, one of which is back pain, especially in the third trimester. If not addressed, back pain can disrupt daily activities and reduce the quality of life of pregnant women. One non-pharmacological intervention to reduce back pain is the red ginger warm compress therapy. Red ginger contains essential oils that are warm, thus increasing blood flow, helping muscle relaxation, and reducing pain. Objective: This study aims to determine the effectiveness of giving a red ginger warm compress in reducing back pain in pregnant women in the third trimester. Methods: This study is a quasi-experimental study using a one-group pretest-posttest design, with a sample of 32 pregnant women in the third trimester. Sampling used non-probability sampling with purposive sampling technique. The research instrument includes an observation sheet using the Numeric Rating Scale (NRS) for pain. Results: The results show a significant decrease in back pain scores among pregnant women p<0,001, with baseline back pain scores of 4,56±1,900 and after therapy 2,47±1,344. Conclusion: The results of this study indicate that red ginger warm compress therapy is effective in reducing back pain intensity among pregnant women in the third trimester. Therefore, red ginger warm compress therapy can be recommended as a non-pharmacological intervention to help alleviate back pain intensity in this population.